Propuesta de diseño de complejo recreativo para la parroquia de Ambatillo, cantón Ambato. - Páez Tenecota, César Paúl (2025)
The design of a recreational complex for the recreation of the inhabitants of the Ambatillo parish, in the Ambato canton, arises in response to the lack of adequate infrastructure for recreational and social recreation activities in the area. This deficit has limited the community's opportunities to enjoy spaces that promote coexistence, health and well-being. The main objective of this project is to design a complex that meets these needs, promoting a healthy and accessible environment for all inhabitants. The central hypothesis of the study maintains that the implementation of a welldesigned and sustainable recreational complex will not only improve the quality of life of the residents of Ambatillo, but will also contribute to the social and economic development of the parish. To defend this idea, a methodology was carried out based on field studies, surveys and interviews with inhabitants, complemented with a documentary and observational analysis of successful recreational facilities both nationally and internationally. The study identified the recreational needs and preferences of the community, allowing a detailed architectural design to be developed that includes sports areas, green areas, and rest and play spaces. Sustainability criteria were considered, such as the efficient use of resources and waste management, as well as the integration of sustainable materials in construction. In addition, aspects of universal accessibility and compliance with municipal regulations were guaranteed. The results obtained showed high acceptance and enthusiasm on the part of the community towards the project, highlighting the importance of having spaces that promote social interaction and recreation in a safe and accessible environment. Thus concluding that the creation of the recreational complex will not only meet the current needs of the inhabitants, but will also provide a replicable model for other rural areas of the country, thus promoting sustainable and equitable development.